Anastasia G. Yangaki, Ceramics in Plain Sight: The Bacini of the Churches of Crete. “Reflections” of the Late Medieval and the Early Modern Material Culture of the Island. Vol. 1. The Regional Unit of Chania. - Armstrong, Pamela (Journal of Greek Archaeology, 2022)
Anastasia G. Yangaki, Ceramics in Plain Sight: The Bacini of the Churches of Crete. “Reflections” of the Late Medieval and the Early Modern Material Culture of the Island. Vol. 1. The Regional Unit of Chania. pp. 352, 311 figs. Athens: Institute of Historical Research, National Hellenic Research Foundation, 2021. ISBN 978-960-7905-70-3, paperback €40.